Electric arc furnace granulated slag for sustainable concrete. (1st October 2016) - Coppola, Luigi; Buoso, Alessandra; Coffetti, Denny; Kara, Patricia; Lorenzi, Sergio
Highlights: Eco-sustainable concrete with EAF granulated slag aggregates. Partial replacement of natural aggregates with EAF granulated slag at level of 15%. Improved rheological/physical/mechanical properties of concrete. Abstract: This paper deals with the use of industrial by-products from electric arc furnace (EAF) granulated slag for the partial replacement of natural aggregates commonly used to manufacture concrete. Three different gradings of EAF granulated slag were considered. The rheological and mechanical properties of concrete manufactured with a partial replacement of natural aggregates with slag were determined. Dry shrinkage of hardened concrete was evaluated. Results indicated that the maximum percentage of natural aggregate that can be replaced with EAF granulated slag is about 15% in order to limit the superplasticizer dosage required to attain the same workability class of the reference concrete mix at the end of the mixing procedure. The higher the percentage of granulated slag was, the higher the density, the elastic modulus in compression and the compressive strength of the concrete were. Dry shrinkage of the concrete increased by adding a greater amount of EAF granulated slag.